PENGARUH KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII MTS HIDAYATUL ATHFAL - M. Luqman Hakim; Dewi Azizah; M. Najibufahmi (LPPM Universitas Bina Bangsa, 2022)
The purpose of the research conducted here is to determine the significant effect of learning independence on student achievement in class VII MTS Hidayatul Athfal. This research is an ex-postfacto study with quantitative methods which are defined as research methods used to examine certain populations or samples. The population in this study were seventh grade students of MTs Hidayatul Athfal in the 2020/2021 academic year. Through purposive sampling technique, namely taking samples with certain considerations. This regional sampling technique is used to determine samples that have special characteristics according to the research objectives, so that they can answer the research problems carried out. This study uses data collection techniques with the questionnaire method and the test method. For data analysis, we can use the average difference test with hypothesis testing (Prerequisite test). That is, there is a positive influence between learning independence on the learning achievement of class VII students of MTs Hidayatul Athfal for the 2020/2021 academic year